EFEKTIVITAS PELAYANAN PUBLIK MENGENAI PERSIDANGAN TELEKONFERENSI DI RUMAH TAHANAN KELAS 1 MAKASSAR: (Perspektif Hukum Islam) - Sartika Dewi,; Hisbullah, (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
This study aims to examine the effectiveness of public services regarding teleconference trials at Makassar Class I Detention Center from the Perspective of Islamic Law. In answering these problems, the author uses a normative syar`i approach and an empirical juridical approach. The method of data collection is done by way of interviews, observation, documentation, and literature study. The results of the study show that (1) The teleconference trial was held based on a circular letter from the Supreme Court Number: 379/DJU/PS.00/03/2020 which aims to be a guide in carrying out the criminal case trial process by teleconference during the Covid-19 pandemic. The procedures or stages of carrying out criminal case trials by teleconference at the Makassar Class 1 Detention Center, namely trial scheduling, preparation of facilities and infrastructure, notification to related parties, escorting detainees and conducting trials. (2) Public services regarding teleconference trials at Class 1 Makassar Detention Center have not been effective because in reality, public services related to teleconference trials have not reflected the implementation of the principles of public service. In this case, several principles and principles of public service that are not yet relevant can be found in the principles of accessibility, openness and transparency, efficiency and effectiveness as well as security and privacy of the accused. (3) Public services in teleconference trials are recommended in Islam as a form of providing assistance and providing convenience to service recipients, in this case detainees and convicts conducting teleconference trials, both in conducting teleconference trials and in applying relevant public service principles and principles. As providing assistance and convenience is something that is recommended (sunnah) for Muslims and get rewards from Allah SWT.